Cardiovascular Mortality Risk in Patients with Bladder Cancer: A Population-Based Study - Shunde Wang; Chengguo Ge; Junyong Zhang (Journal of Cardiovascular Development and Disease, 2022)
Background: The purpose of this study was to evaluate the risk of cardiovascular mortality (CVM) among patients with bladder cancer (BC). Methods and Materials: Data were collected from the Surveillance, Epidemiology, and End Results (SEER) database for patients who were diagnosed with BC by pathology between 2000 and 2016. The standardized mortality rate (SMR) was calculated based on reference data from the general population. Nelson–Aalen cumulative hazard curves were used to assess the risk of experiencing CVM in BC patients. Multivariate competing risk models were performed. Results: In total, data from 237,563 BC patients were obtained from the SEER database for further analysis, of which 21,822 patients experienced CVM; the overall SMR for CVM in BC patients was 1.16 (95% CI: 1.14–1.17). Age, race, sex, year of diagnosis, histologic type, summary stage, surgery, marital status, and college education level were independent predictors of CVM in patients with BC. Conclusions: Patients with BC have a significantly increased risk of experiencing CVM compared to the general population. Pre-identification of high-risk groups and cardiovascular protection interventions are important measures to effectively improve survival in this group of patients.